Beyond gaming: Linking flow, brand attitudes, and purchase intent in realistic and emergent three-dimensional virtual environments. Issue 6 (2nd December 2019) - Hooker, Robert; Wasko, Molly; Paradice, David; Teigland, Robin; Hofacker, Charles
Abstract : Purpose: The purpose of this paper is to test flow as a construct distinctly separate from its antecedents, and the resulting impact on brand attitudes and purchase intent within realistic online shopping three-dimensional virtual environments (3-DVEs). Design/methodology/approach: This research utilizes a field study, combined with a survey research design of 348 3-DVE participants. Findings: The findings reveal that flow is not a unidimensional construct but rather, a mental state that should be measured separately from its antecedents, with the possibility that certain antecedents may be more relevant than others in different activities. Furthermore, the authors received strong support for the overarching hypothesized model separating the nine dimensions associated with engagement in an activity as antecedents of flow, which, in turn, influences brand attitude and thereafter purchase intention. Research limitations/implications: This study was limited to one type of activity within one 3-DVE but is balanced by the difficulty in gaining access to organizations and computer-mediated environments of this type for examining such phenomena. Practical implications: Businesses using 3-DVEs to market brands should focus their efforts on creating highly enjoyable experiences that result in the feeling of a loss of sense of time for the participants in order to ultimately positively influence purchase intentions. Originality/value: Prior research focused on fantasy-based, game-oriented environments, while also neglecting to test all elements of flow, examining "similar to flow" constructs or measuring flow as a unidimensional construct.